KOMUNIKASI INOVASI USAHA SABLON KARANG TARUNA DALAM MENINGKATKAN PENGHASILAN MASYARAKAT DESA PARAIKATTE KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The main problem in this study is how to communicate innovations in the youth screen printing business in increasing the income of the people of Paraikatte Village, Gowa Regency. The main problem is further divided into two sub-problems, namely 1) How is the communication process of the youth screen printing business to the Paraikatte Village community? 2) How is the implementation of diffusion theory in the communication process of the youth screen printing business innovation to the people of Paraikatte Village. The type of research used is qualitative research with a scientific approach to communication. Data collection methods used are observation, interviews, and documentation. The technique of testing the validity of the data is done by triangulation. The communication process of the screen printing business innovation carried out by the youth organization to the Paraikatte Village community went through several stages, namely the stages of knowledge, persuasion, decision, and confirmation. The success factors in the communication process of the youth screen printing business innovation to the Paraikatte Village community reap positive results. The success factors of the screen printing business communication are the characteristics of innovation that are fulfilled, communication channels that can reach a broad public, the efforts of agents, and the modern social system of society.